Use of modeling and simulation: Tools necessary for the formation of a virtual library for practical disciplines in higher education - del Rio, Daniel Guzmán; Cisneros, Edry Antonio Garcia; Junior, Edward Pinto Pimenta; Cabrera, Daniel Guzman; Ruano, Joycet Ramirez; Sobrinho, Angilberto Muniz (Seven Editora, 2024)
The use of modeling and simulation tools in current education systems has become fundamental pieces in student learning, increasing the possibility of acquiring knowledge and practical skills. In the present work, the authors present the didactic proposal for the development of a virtual library using Matlab® tools to be used in activities of practical disciplines in higher education, which can be extended to other types of education, such as technological. The discipline of Control Systems in the Electrical Engineering course is taken as an example for the development, dividing the methodological procedure for its realization into stages. In these stages, the purpose of offering students specific and ready-made virtual resources are designed that can also be used in other disciplines, with wide iterativeness, which undoubtedly improves the acquisition of knowledge and improves learning. The modular organization of the library, with the creation of specific subsystems in blocks, allows for a personalized approach that is adaptable to the individual knowledge needs of students. This tool can be part of an active teaching methodology. DOI:https://doi.org/10.56238/sevened2024.026-038